Knee muscle strength, body composition, and balance performance of youth soccer players - França, C.; Martins, F.; Lopes, H.; Marques, A.; de Maio Nascimento, M.; Przednowek, K.; Ihle, A.; Campos, P.; Gouveia, É. R. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Muscle strength and balance abilities have been related to game performance injury prevention. This study aimed to (1) assess knee muscle strength performance based on intra- and inter-limb asymmetries, (2) investigate the relationships between knee muscle strength, body composition, and balance, and (3) analyze the variance in the overall stability index (OSI) explained by knee muscle strength indicators after controlling for age and body composition.